Stable Isotopic Tracing—A Way Forward for Nanotechnology - Gulson, Brian (National Institute of Environmental Health Sciences, 2006)
Numerous publications and reports have expressed health and safety concerns about the production and use of nanoparticles, especially in areas of exposure monitoring, personal use, and environmental fate and transport. We suggest that stable isotopic tracers, which have been used widely in the earth sciences and in metabolic and other health-related studies for several decades, could be used to address many of these issues. One such example we are pursuing is the use of stable isotopes to monitor dermal absorption of zinc and titanium oxides in sunscreen preparations and other personal care products. Other potential applications of this tracing approach are discussed.